Display of Protectionism in Modern Tourist Branch - L. G. Karanatova; A. V. Evsyukov (Управленческое консультирование, 2018)
The necessity to protect the interests of the Russian Federation in the context of an aggressive sanctions situation determine the need to take protecting measures for the domestic market and its consumers. The research analyzes key economic and political developments that have affected to stability and structure both inbound and outbound tourist flow. Measures taken to stabilize and strengthen domestic tourism are observed. The issue of rationality of measures aimed at increasing the domestic tourism volume from the import substitution point of view are also raised.